Augmentation of DFIG and PMSG Wind Turbines Transient Performance Using Different Fault Current Limiters - Kenneth E. Okedu (Energies, 2022)
The technology of variable speed wind turbines is very promising in renewable power generation. It is imperative for wind turbines to gain control after grid disturbances and contribute to the stability of power grids as part of the requirements of grid codes set by grid operators in operating wind farms. Fault current limiters (FCLs) are capable of augmenting the performance of wind turbines during grid disturbances. In this article, the augmentation of the Doubly Fed Induction Generator (DFIG) and the Permanent Magnet Synchronous Generator (PMSG) wind turbines, which are the two most popular variable speed wind turbines, is presented. The evaluation of both wind turbines was performed considering the Series Dynamic Braking Resistor (SDBR), Bridge Fault Current Limiter (BFCL) and the Capacitive Bridge Fault Current Limiter (CBFCL). The modeling of the FCLs in the wind turbines was derived for steady state and grid disturbances so that their dynamic behavior could be understood. The grid voltage variable was employed as the signal for switching the FCLs in both wind turbines during grid disturbances. Moreover, a scenario with no control using the FCLs was also carried out for both wind turbines. The performance of the FCLs in both wind turbines was analyzed and compared using a severe three-phase to ground fault at their terminals. For effective comparison, the same conditions of operation were used in investigating the performance of the FCLs control strategies in both wind turbines during grid disturbances. The study was conducted using Power System Computer-Aided Design and Electromagnetic Transient including DC (PSCAD/EMTDC) environment.